A Rosaceae Family-Level Approach To Identify Loci Influencing Soluble Solids Content in Blackberry for DNA-Informed Breeding. Issue 10 (1st October 2020) - Zurn, Jason D; Driskill, Mandie; Jung, Sook; Main, Dorrie; Yin, Melinda H; Clark, Melissa C; Cheng, Lailiang; Ashrafi, Hamid; Aryal, Rishi; Clark, John R; Worthington, Margaret; Finn, Chad E; et al.
Abstract: A Rosaceae family-level candidate gene approach was used to identify genes associated with sugar content in blackberry ( Rubus subgenus Rubus ). Three regions conserved among apple ( Malus × domestica ), peach ( Prunus persica ), and alpine strawberry ( Fragaria vesca ) were identified that contained previously detected sweetness-related quantitative trait loci (QTL) in at least two of the crops. Sugar related genes from these conserved regions and 789 sugar-associated apple genes were used to identify 279 Rubus candidate transcripts. A Hyb-Seq approach was used in conjunction with PacBio sequencing to generate haplotype level sequence information of sugar-related genes for 40 cultivars with high and low soluble solids content from the University of Arkansas and USDA blackberry breeding programs. Polymorphisms were identified relative to the 'Hillquist' blackberry ( R. argutus ) and ORUS 4115-3 black raspberry ( R. occidentalis ) genomes and tested for their association with soluble solids content (SSC). A total of 173 alleles were identified that were significantly (α = 0.05) associated with SSC. KASP genotyping was conducted for 92 of these alleles on a validation set of blackberries from each breeding program and 48 markers were identified that were significantly associated with SSC. One QTL, qSSC-Ruh-ch1.1, identified in both breeding programs accounted for an increase of 1.5 °Brix and the polymorphisms were detected in the intron space of a sucrose synthase gene. This discovery represents the first environmentally stable sweetness QTL identified in blackberry. The approach demonstrated in this study can be used to develop breeding tools for other crops that have not yet benefited directly from the genomics revolution.